Knowledge, attitude, and practice related to oral health among undergraduate Ayurvedic students in Davangere city: a cross-sectional survey - Yavagal, Puja C.; H. S., Mahalaxmi; B., Sapna; Maruthi, Sushma G.; D. N., Vinitha; Paramashetti, Sneha (International Journal Of Community Medicine And Public Health, 2024)
Background: To assess the knowledge, attitude, and practice related to oral health among undergraduate Ayurvedic students in Davangere city. Methods: A cross-sectional questionnaire survey was conducted involving 584 Ayurvedic undergraduate students from three Ayurvedic colleges in Davangere city. A 25-item pre-validated questionnaire was used to assess the knowledge, attitude, and practice related to oral health. Responses to knowledge scores were assigned weights and summed up to obtain total knowledge scores which ranged between 0-23, and categorized as good (0-7.6), fair (7.7-15.2), and poor (15.3-23). Statistical analyses: Responses were expressed in percentages. Man-Whitney U test, Kruskal Wallis ANOVA, and Pearson’s/Spearman correlation tests were used for data analysis by setting the significance level at p<0.05. Results: The response rate was 83.4%. The mean age of study participants was 21.30±1.62 years. The majority were females (67%). The mean knowledge score was 12.9±3.37 which reflected fair oral health-related knowledge which on comparison was similar across different sex (p=0.14) and year of study (p=0.82). There was no correlation between knowledge scores and age (r=0.14, p=0.74) or sex (r=0.06, p=0.14). The majority (>90%) felt the need for collaboration with dentists and up gradation of the oral health care section in the Ayurvedic curriculum. Conclusions: The knowledge, attitude, and practices related to oral health care was fair among Ayurvedic students in Davangere city.